Efektivitas Kinerja Aplikasi SIAPIK dalam Pencatatan Keuangan Usaha Sektor Manufaktur - Islami, Erni Mutiara; Suwondo, Sulistia; Sembiring, Etti Ernita; Burhany, Dian Imanina; Nurmalina, Rina (Indonesian Accounting Literacy Journal, 2025)
This study aims to assess the effectiveness of the SIAPIK application in assisting financial record-keeping for micro-enterprises in the manufacturing sector. The research was conducted using a qualitative descriptive approach through a case study on Besty Dimsum, a micro business that had not previously implemented structured financial reporting. Data were collected through interviews, observation, and documentation. The application was used to record business transactions, generate financial statements, and evaluate the ease and accuracy of its features. Results showed that SIAPIK facilitated structured and standardized financial reporting aligned with SAK EMKM. While the system was generally easy to use, some limitations were identified, including the lack of decimal input and insufficient in-app instructions. Overall, SIAPIK proved to be a useful and accessible tool for improving financial documentation in micro-manufacturing enterprises.